(untitled) - Datta, Sanjay (St. Louis, 1996)
Anesthetic and obstetric management of high-risk pregnancy, particularly, gave me an enormous aumount of satisfaction because of the understanding of the need for close communication between two specialties, anesthesiology and obstetric, not only to take care of the sick parturient but also to deliver a healthy baby.
Keywords: Gây mê trong sản khoa,Mang thai,Anesthesia in obstetrics,Pregnancy; Các biến chứng,Complications